Carbapenem resistant Enterobacteriaceae from port areas in São Paulo State (Brazil): Isolation and molecular characterization - Andrade, Vanessa Costa [UNESP]; Caetano, Tânia; Mendo, Sónia; Oliveira, Ana Júlia Fernandes Cardoso de [UNESP] (Elsevier, 2020)
Coastal areas with important economic activities have high levels of contamination by metals, pathogenic bacteria, among other contaminants. The emergence of antibiotic-resistant bacteria is a global problem of public health. Carbapenem resistant Enterobacteriaceae (CRE) are a serious threat. The occurrence of carbapenem resistant bacteria was investigated in waters and sediments of a Brazilian coastal area, characterized by high levels of contamination. The samples of water and sediment were collected in two areas of the coast of São Paulo (Brazil). The study involved the characterization of the molecular mechanisms associated with the carbapenem resistance phenotype. No genes were detected for β-lactamases but the absence and/or presence of mutations in outer membrane proteins (OMPs) may justify the detected phenotype. The presented results show the need for further studies that allow a review of the current legislation and the importance of the reevaluation of monitoring policies of these environments.
Keywords: Bacterial resistance; Co-selection; Coastal contamination; Port contamination